(untitled) (Third Sector Social Economic Review, 2026)
Traditionally, economic growth has been defined by production expansion and per capita income increases. The neoclassical theory, however, hypothesizes that growth would naturally reduce inequality. With deepening disparities across the world, the term “inclusive growth” has been coined to emphasize social justice and equal opportunities alongside quantitative growth. This study presents a comparative analysis from 2002 to 2023 for France, the UK, Israel, Italy, Sweden, and Türkiye using four inclusive growth indices. Evaluations using composite methods and PCA reveal that methodological approaches, specifically indicator selection and weighting, substantially affect how a country’s internal progress is reflected. Because each country is normalized within its own historical trajectory, results reflect internal improvement rates rather than absolute cross-country rankings. For instance, Türkiye exhibits the highest relative momentum in the growth-oriented Hakimian index, while Sweden demonstrates greater internal stability in the sustainability-focused UNCTAD index. In contrast, mature economies often show lower scores in growth-centric indices due to the “saturation effect” of established structures. Findings indicate that despite strong absolute growth, the perceived rate of progress in countries like Türkiye and Israel varies significantly depending on the index employed, especially when prioritizing structural challenges like income inequality over quantitative expansion.